1978
DOI: 10.1113/jphysiol.1978.sp012310
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetry of the hexose transfer system in human erythrocytes. Experiments with non‐transportable inhibitors.

Abstract: SUMMARY1. The asymmetrical nature of sugar affinity for the hexose transfer system in human red cells has been demonstrated using purified 4,6-O-ethylidene-oz-D-glucopyranose (ethylidene glucose) to inhibit the exchange of glucose, 3-0-methyl glucose and galactose.2. The half-saturation concentration for ethylidene glucose inside the cell is estimated at ca. 110 mm whereas on the outside the value for exchange inhibition is ca 11 mM.3. The asymmetries of affinities of two related non-transportable inhibitors 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
34
1

Year Published

1979
1979
2004
2004

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 9 publications
7
34
1
Order By: Relevance
“…The effect of 200 mM-ethylidene glucose inside the cells was less than that of 50 mm outside. Although marked, this asymmetry was less than that obtained by Baker et al (1978) 20 mm the saturation fraction of 3-0-methyl glucose for human cells is greater than for new-born guinea-pig cells and this partly compensates for the lower VEX in human cells.…”
Section: -0-methyl Glucose Exchangementioning
confidence: 60%
See 3 more Smart Citations
“…The effect of 200 mM-ethylidene glucose inside the cells was less than that of 50 mm outside. Although marked, this asymmetry was less than that obtained by Baker et al (1978) 20 mm the saturation fraction of 3-0-methyl glucose for human cells is greater than for new-born guinea-pig cells and this partly compensates for the lower VEX in human cells.…”
Section: -0-methyl Glucose Exchangementioning
confidence: 60%
“…When inhibitors of hexose exchange are present, a relatively simple treatment (Baker et al 1978) predicts that the reciprocal of the exchange flux should be a linear function of the inhibitor concentration and that such a line should intercept a line through 1/VEX parallel to the abscissa at a point corresponding to the half-saturation concentration for the inhibitor.…”
Section: -0-methyl Glucose Exchangementioning
confidence: 99%
See 2 more Smart Citations
“…Examination of these results and others already published (Baker, Basketter & Widdas, 1978) has shown that they are difficult to interpret by simple carrier kinetics (Widdas, 1985). The collection of data from earlier experiments and the filling in with Sen-Widdas experiments at 16-17°C for 3-0-methyl glucose exits, not previously available, has provided data which could be used in a fuller appraisal of the results in terms of the asymmetric carrier equations of Regen & Tarpley (1974) which were shown by Widdas (1980) to be applicable to experiments with non-transportable inhibitors.…”
Section: G F Baker And-w F Widdasmentioning
confidence: 99%